UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA SMAN 2 KOTA BENGKULU MELALUI EKSTRAKULIKULER RISMA AL-ASHR - Nur Layli Hidayah (UIN Fatmawati Sukarno Bengkulu, 2017)
The purpose of this study is to determine the activities and achievements of learning contained in RISMA AL ASHR, what are the supporting and inhibiting factors and know the efforts to improve student achievement through extracurricular RISMA AL ASHR. This type of research uses qualitative descriptive qualitative research method (qualitative research). Infor- mants of this study are 10 RISMA AL ASHR Board, 5 PAI Teachers and 2 Pementors. This research takes time during March s.d June 2017. The data collection procedure of researcher use observation, interview and documentation. Data analysis that researchers do is through the stages of data collection, data reduction, display data and conclusions. From the results of the research so far it can be concluded that the activities of RISMA has run entirely, except for 1 rabbana activities that did not happen. What is interesting is that RISMA managers and builders always carry out an evaluation of the implementation of RISMA activities, this is very much related to forming students who excel as outputs. So that output is a proof of the number of outstanding students in RISMA. The prominent learning achievement in this RISMA student in the form of academic achieve- ment and nonakademik